The Promising Ethics And Competitive Advantage On Higher Education As A Part Of International Collaboration Programs - Prihartono Prihartono (Green Publisher Indonesia, 2021)
Promises ethics in service triangle context on higher education can be met if performance improves superior performance and be given the implications for competitive advantage. The purpose of this study was to analyze and determine promising ethics in service marketing triangle and competitive advantage of higher education. The research method used is survey method, namely descriptive and explanatory. The number of respondents in the study is 330 students of the polytechnic in West Java, which is determined by sampling technique, which is cluster proportional random sampling. The hypothesis testing was done using a multivariate statistical test of the Partial Least Square (PLS). The data processing was done with smartPLS 2.0 programs and Statistical Programs of Social Science (SPSS) for Windows. The results show that: The promising ethics in service triangle context and competitive advantage influence as well but not quite good. The promising ethics in service marketing triangle context can be met also if performance improves international collaboration on higher education as well, so that promises ethics can be achieved optimally and be given the implications for competitive advantage of higher education.